Functional Role of miR-499a-5p in the Development of Gastric Cancer - Cuiling Lu; Chengwang Guo; Cuihua Wu; Liping Zhang; Xiaoling Liu; Shoucun Guo (The Turkish Journal of Gastroenterology)
Background/Aims: Gastric cancer (GC) is a highly prone malignant tumor, which has attracted wide attention. This study investigated the expression and clinical value of miR-499a-5p in GC.